Morphological characterization of different phytophthora isolates from major crops and soil - Catiempo, Rose L. (2007)
Six Phytophtthora isolates were obtained from different plant sources (avocado, cacao, coconut, and durian) and soil in Davao City. Colony growth and characteristics in the isolates had stellate and slightly colony patterns except the isolate from coconut which had a rosette growth pattern. All colonies are white, cottony and had an irregular-wavy margin. All isolates had striated colonies except the isolate from coconut. All had pronounced aerial mycelium except the isolate from cacao which was fine-textured and flat on the agar. Phytophthora isolate from coconut grew the fastest while the isolate from cacao was the slowest. On spore production, the isolates from durian stem canker and fruit rot were the highest and the cacao isolate was the slowest. On spore morphometrics, phytophthora from soil had the longest sporangium length (51.61 7.06m), Phytophthora from avocado had the biggest papilla (average of 6.40 2.04m in length and 8.68 1.75m in width) and the Phytophthora from cacao had the biggest pedicel (average length of 5.90 1.70m and a width of 7.12 1.72m). variations in shape and size of sporangia are not only observed among isolates but also observed within the same isolate